Financial performance of the commercial bank in the Kingdom of Saudi Arabia: An empirical insight - Saif, Abdulazeez Yousef Hazzaa (2014)
The purpose of this study is to investigate the financial performances of Saudi commercial banks during the period 2000-2013. A sample of 21 commercial banks comprising of 10 foreign owned banks operating in the country and 11 Saudi domestic banks for the captioned 14 years period have been used in the study. Though there are studies on Saudi domestic commercial banks, no comprehensive evaluation have so far been made by including foreign banks in their sample. The researcher has aimed to fill-in this gap in the literature. Using panel data Linear Multiple Regression model and Ordinary Least Squares have been used in the present study to estimate the impact of the driver ratios like capital adequacy (CAR), asset quality (AQ), operational efficiency (OE), bank size (SIZE), net loan to total deposits (LIQR-1), liquid assets to total assets (LIQR-2). on the financial parameters like Return on Equity (ROE), Return on Asset (ROA), Net Interest Margin (NIM) and Tobin’s Q. The study found that at the pool level, that CAR, OE, SIZE, LIQR-1 LIQR-2 have positive and significant relationship with ROA but AQ has negative and significant relationship with ROA. Similarly, CAR, SIZE and LIQR-2 have positive significant relationship with ROE, whereas LIQR-1 has positive but insignificant relationship with ROE. AQ has negative and significant relationship and OE has negative but insignificant relationship with ROE. All the determinant variables excepting CAR and OE of banks have positive significant relationship with NIM. CAR has positive but insignificant relationship with NIM and OE has negative but significant relationship with NIM. Tobin’s Q has positive significant relationship with LIQR-2. CAR, OE and LIQR-1 have negative insignificant relationship with Tobin’s Q. It's also found that AQ and SIZE have negative but significant relationship with Tobin’s Q. In the case of domestic banks, all independent variables have insignificant impact on all dependent variables, except CAR which has positive and significant relationship with ROA. AQ has negative but significant relationship with ROA, ROE and Tobin’s Q. SIZE has negative significant relationship with Tobin’s Q and LIQR-1 has positive significant relationship with NIM; and LIQR-2 has positive and significant relationship with ROE, and Tobin’s Q. Finally, in the case of foreign banks, all deriver variables have insignificant effect on ROA, ROE, NIM and Tobin’s Q, except CAR, OE and LIQR-1 which have positive and significant relationship with ROA. AQ and LIQR-1 have positive significant relationship with NIM. CAR, AQ and SIZE have negative relationship with Tobin’s Q. LIQR-2 have positive and significant relationship with ROE, NIM and Tobin’s Q.